2017
DOI: 10.1016/j.mayocp.2017.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Gammopathy–Associated Peripheral Neuropathy: Diagnosis and Management

Abstract: Monoclonal gammopathies consist of a spectrum of clonal plasma cell disorders that includes monoclonal gammopathy of undetermined significance (MGUS), multiple myeloma (MM) and Waldenstrom Macroglobulinemia (WM). In this review, we outline the epidemiology, etiology, classification, diagnosis, and treatment of monoclonal gammopathy associated peripheral neuropathy. Monoclonal gammopathy of undetermined significance (MGUS) is relatively common in the general population, with a prevalence of 3–4% among those ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(105 citation statements)
references
References 63 publications
0
99
0
6
Order By: Relevance
“…Finally, we reviewed progression events, which included a mix of risk scores and unique progression patterns, highlighting the importance of careful clinical monitoring of all MGUS patients over time. Additional diagnoses not specifically identified in our study but which also need to be considered include amyloid light‐chain amyloidosis, POEMS (polyneuropathy, organomegaly, endocrinopathy, monoclonal gammopathy, and skin changes), monoclonal gammopathy of renal significance, and other MGUS‐associated disorders …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Finally, we reviewed progression events, which included a mix of risk scores and unique progression patterns, highlighting the importance of careful clinical monitoring of all MGUS patients over time. Additional diagnoses not specifically identified in our study but which also need to be considered include amyloid light‐chain amyloidosis, POEMS (polyneuropathy, organomegaly, endocrinopathy, monoclonal gammopathy, and skin changes), monoclonal gammopathy of renal significance, and other MGUS‐associated disorders …”
Section: Discussionmentioning
confidence: 93%
“…We found that the frequency of paraprotein surveillance increased with consult utilization, such that surveillance testing was more fre- Additional diagnoses not specifically identified in our study but which also need to be considered include amyloid light-chain amyloidosis, POEMS (polyneuropathy, organomegaly, endocrinopathy, monoclonal gammopathy, and skin changes), monoclonal gammopathy of renal significance, and other MGUS-associated disorders. [14][15][16][17] This retrospective study is limited by what is available in the elec- consultation may vary at different health care centers. Extension of this work to an analysis of VA-wide data would provide larger numbers and increased diversity to strengthen these initial observations.…”
Section: Mangiacavalli S Et Al Demonstrated That the Risk Of Bone Lesmentioning
confidence: 99%
“…Treatment of MM does not improve paraproteinemic neuropathy, and therapies targeted at the neuropathy are not well established. 3,4,9 Radiculopathy in MM is generally a consequence of either mechanical compression (by, for example, vertebral plasmacytoma, foraminal stenosis due to pathologic fracture, or vertebral body collapse) or LMD. Uncommonly, nerve root involvement has been associated with MM-related polyneuropathy, as seen in previous studies that relied on pathologic examination rather than EMG/NCS data.…”
Section: Discussionmentioning
confidence: 99%
“…In immunoglobulin light chain amyloidosis, 5% have an IgM monoclonal protein . The mechanism of the neuropathy is thought to be demyelination due to direct binding of the antibody to myelin‐associated glycoprotein …”
Section: Disease Overviewmentioning
confidence: 99%